Combined administration of levetiracetam and valproic acid attenuates age‐related hyperactivity of CA3 place cells, reduces place field area, and increases spatial information content in aged rat hippocampus. Issue 12 (14th July 2015) - Robitsek, Jonathan; Ratner, Marcia H.; Stewart, Tara; Eichenbaum, Howard; Farb, David H.
ABSTRACT: Learning and memory deficits associated with age‐related mild cognitive impairment have long been attributed to impaired processing within the hippocampus. Hyperactivity within the hippocampal CA3 region that is associated with aging is mediated in part by a loss of functional inhibitory interneurons and thought to underlie impaired performance in spatial memory tasks, including the abnormal tendency in aged animals to pattern complete spatial representations. Here, we asked whether the spatial firing patterns of simultaneously recorded CA3 and CA1 neurons in young and aged rats could be manipulated pharmacologically to selectively reduce CA3 hyperactivity and thus, according to hypothesis, the associated abnormality in spatial representations. We used chronically implanted high‐density tetrodes to record the spatial firing properties of CA3 and CA1 units during animal exploration for food in familiar and novel environments. Aged CA3 place cells have higher firing rates, larger place fields, less spatial information content, and respond less to a change from a familiar to a novel environment than young CA3 cells. We also find that the combination of levetiracetam (LEV) + valproic acid (VPA), previously shown to act as a cognitive enhancer in tests of spatial memory, attenuate CA3 place cell firing rates, reduce place field area, and increase spatial information content in aged but not young adult rats. This is consistent with drug enhancing the specificity of neuronal firing with respect to spatial location. Contrary to expectation, however, LEV + VPA reduces place cell discrimination between novel and familiar environments, i.e., spatial correlations increase, independent of age even though drug enhances performance in cognitive tasks. The results demonstrate that spatial information content, or the number of bits of information encoded per action potential, may be the key correlate for enhancement of spatial memory by LEV + VPA. © 2015 Wiley Periodicals, Inc.